2020
DOI: 10.1097/01.asw.0000655472.02780.e0
|View full text |Cite
|
Sign up to set email alerts
|

Hand Dermatitis in Nursing Students

Abstract: OBJECTIVE To determine the frequency of self-reported hand dermatitis and the factors influencing its prevalence among nursing students. METHODS Researchers collected demographic data and used a self-assessment form to identify dermatologic symptoms. The questionnaires were distributed to the students and collected again after the students completed the forms. RESULTS Hand dermatitis was present in 20.9% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 26 publications
0
19
2
Order By: Relevance
“…26,[29][30] However, some studies reported that prevalence of HD was not associated with gender. [31][32] The results of our study showed that there was a positive correlation between age of HCWs and the prevalence of HD, and the highest prevalence of HD was found in HCWs older than 40 years. Two studies conducted on Danish children reported that children with a higher age were at a higher risk of developing HD.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…26,[29][30] However, some studies reported that prevalence of HD was not associated with gender. [31][32] The results of our study showed that there was a positive correlation between age of HCWs and the prevalence of HD, and the highest prevalence of HD was found in HCWs older than 40 years. Two studies conducted on Danish children reported that children with a higher age were at a higher risk of developing HD.…”
Section: Discussionmentioning
confidence: 59%
“…Lampel et al 11 , found no significant association between the prevalence of HD in inpatient nurses working at an academic hospital and their working hours per week. By contrast, Özyazicioğlu et al 32 , reported that the incidence of HD in the fourth-year nursing students was significantly higher than the third-year students. They attributed this finding to the higher working hours of the fourth-year students compared with the third-year students, which was inconsistent with our findings.…”
Section: Discussionmentioning
confidence: 89%
“…5 Hands dermatitis is a very common reason for seeking dermatological care, but pustular lesions of the dorsum of hands are rarely described. 6 Sensitization to rubber components is a main cause of hand dermatitis. Pustular contact dermatitis, however, is not a typical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic dermatitis is more common on the dorsum of the hands and can appear around the wrists because the skin is thinner and there is a greater penetration of allergens in these locations. 2,3 Although 2% to 10% of all people will develop eczema on their hands at some point in their life, 2 this rate varies in the range of 30% to 69% among nurses working at hospitals. 3 Hand dermatitis is one of the most significant workplace health problems in clinical nursing, and it usually presents in the form of redness, itching, dryness, or vesiculation.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although 2% to 10% of all people will develop eczema on their hands at some point in their life, 2 this rate varies in the range of 30% to 69% among nurses working at hospitals. 3 Hand dermatitis is one of the most significant workplace health problems in clinical nursing, and it usually presents in the form of redness, itching, dryness, or vesiculation. 4 With the onset of the COVID-19 pandemic, the increased use of antiseptics/hand disinfectants and frequent exposure to water and soap brought greater eczema risk.…”
Section: Introductionmentioning
confidence: 99%